Application of the Braden Scale Assessment Instrument to Pressure Injury Events at Banjarmasin Islamic Hospital - Noorhasanah, Evy; Anita Agustina; Milasari, Milasari; Agustini, Metti; Pramono, Yosra Sigit; Lisnawati, Ica; Millati, Rida` (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
These pressure sores can occur in patients who are in a sitting or lying position for a long time. If this occurs, healing will be difficult, costs will be high, hospital stay will be extended, and mortality will increase. Pressure ulcers can be detected using the Braden scale. The Braden Scale shows higher validity and reliability when compared with other measuring instruments. At the Banjarmasin Islamic Hospital, a scale is not yet used and nurses tend to carry out clinical judgment in assessing the risk of pressure ulcers in patients, so errors often occur in risk assessment in patients. This training aims to enable nurses to apply risk assessments to patients using the Braden scale. carried out for 2 days at the Banjarmasin Islamic Hospital totaling 25 people. The training method uses lectures, discussions and role plays. Evaluation by means of pre and post tests. In conclusion: Participants' knowledge and understanding in the application of risk assessment with the Braden scale increased after attending the training.